2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR) 2013
DOI: 10.1109/icorr.2013.6650400
|View full text |Cite
|
Sign up to set email alerts
|

Lever-actuated resonance assistance (LARA): A wheelchair-based method for upper extremity therapy and overground ambulation for people with severe arm impairment

Abstract: People with severe arm impairment have limited technologies available for retraining their arms, and, if they also have difficulty walking, they often cannot effectively use a manual wheelchair because they cannot grasp and push the pushrim. We are using Lever-Actuated Resonance Assistance (LARA) to solve these problems. A LARA-based device can attach to a manual wheelchair and allow it to be used by people with severe arm weakness in a stationary exercise mode, or for self-powered overground ambulation. LARA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Our prior analysis shows that operating a LARAbased wheelchair at its resonant frequency could theoretically reduce the RMS torque required for sustained over-ground movement by upwards of 50%. 26 Our LARA-based device is an adaptation of the Resonating Arm Exerciser (RAE), a device designed for repetitive arm movement training after stroke. 27 RAE consists of a lever rigidly connected to one wheel of a wheelchair, a splint for attaching the impaired arm to the lever, and elastic bands between the lever and the frame of the chair, which makes the lever system resonant.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior analysis shows that operating a LARAbased wheelchair at its resonant frequency could theoretically reduce the RMS torque required for sustained over-ground movement by upwards of 50%. 26 Our LARA-based device is an adaptation of the Resonating Arm Exerciser (RAE), a device designed for repetitive arm movement training after stroke. 27 RAE consists of a lever rigidly connected to one wheel of a wheelchair, a splint for attaching the impaired arm to the lever, and elastic bands between the lever and the frame of the chair, which makes the lever system resonant.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous pilot study with a stationary version of LARA, a device called RAE, we found that users with severe arm impairment (FM score = 21.4 points ± 8.8 SD out of 66) could move the levers and synchronize to the resonance of the device, created by springs attached to the levers, and that repeatedly moving the levers had a therapeutic benefit [6], [7]. We then made RAE into LARA by incorporating one-way bearings into the levers and found that people with severe arm impairment could also drive LARA overground [8], [9]. This is important clinically because it means that stroke inpatients could potentially bimanually propel their wheelchairs, greatly increasing their arm activity beyond the low amounts that are typical during routine therapy [10], and thus potentially enhancing use-dependent plasticity [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, machine-assisted exercise has numerous potential advantages, including motivational aspects, the ability to measure changes, telerehabilitation capabilities, and the addition of video games, a possibility that we have begun to explore with the RAE. 44 Furthermore, the RAE group in the present study reported their therapy to be significantly less stressful than the conventional therapy group, which suggests that a machine-based approach may also reduce patient anxiety during exercise. In a separate study with nonimpaired users, the participants perceived time as moving more quickly when exercising with the RAE, highlighting again possible beneficial psychophysical effects of resonance entrainment.…”
Section: Discussionmentioning
confidence: 51%
“…Further, participants in the conventional therapy group performed their exercises at home without human assistance, suggesting conventional home-based therapy is feasible for this population. However, machine-assisted exercise has numerous potential advantages, including motivational aspects, the ability to measure changes, tele-rehabilitation capabilities, and the addition of video games, a possibility we have begun to explore with RAE 44 . Furthermore, the RAE group in the present study reported their therapy to be significantly less stressful than the conventional therapy group, which suggests that a machine-based approach may also reduce patient anxiety during exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation